Zoological wonders in Pliny the Elder Encyclopedia, according to two suggestions of Italo Calvino - Trevizam, Matheus (2015)
In this paper, we would like to present some ideas found in the eighth book of Naturalis Historia, whose authorship is attributed to Pliny the Elder. With this purpose in mind, after contextualizing the Roman writer in his own time, under a human, intellectual and historical point of view, we proceed to the examination of the author’s treatment of the elephants and of several fabulous beings (such as dragons and basilisks), in the same part of the book mentioned. In the first case, similarly to Virgil’s Georgics book IV, which is devoted to the development of apiculture, Pliny shows the animal society on which he has focused his attention as something, at the same time, very close and very far from human culture and feelings. Regarding Plinian treatment of beings which nowadays we would call “monstrous”, because of their lack of proportion, strong hybridization or potential harmfulness to men or other creatures, we realize also that the ancient author seems to write about those prodigies as spontaneously as someone aware of the highly inventive nature of the creative powers in operation in the world. In this movement of looking into the bizarre aspects of the world, Pliny was, later, closely followed by Jorge Luis Borges, author of The book of imaginary beings.